THE EFFECTIVENESS OF ALLIN ESSENTIAL OIL COMPRESSES ON REDUCING BODY TEMPERATURE FOR FEBRILE INFANTS AGED 6-12 MONTHS IN THE POSYANDU BAWAL AREA ENVIRONMENT XIX BELAWAN BAHAGIA IN 2023 - Tasya Emaya Sembiring; Tiarnida Nababan; Liber Febriani Zamago; Yusni Fadilla; Peber Sixma Br Tarigan (PT. Radja Intercontinental Publishing, 2024)
Fever is a condition of increasing body temperature beyond normal limits. Fever can cause damage to the nervous system and cause febrile seizures when the body is above 40°C, so it is very important to take proper and immediate action. Reducing the degree of heat of children who have fever can be physically (nonpharmacological) through evaporation and conduction methods in the application of heat energy. Shallots (Allium cepa ascalonicium variety) is a traditional feverreducing medicine in infants and toddlers. The purpose of this study was to determine the effectiveness of onion compress (Allin essential oil) on reducing body temperature in the Posyandu Bawal Area of Environment XIX Belawan Bahagia in 2023. This study used an experimental quasy research design with a one-group prepost test design. The population in this study amounted to 30 respondents. The sampling method used is nonprobality sampling with a total sampling type of 30 respondents. The method of collecting research data is using observation sheets for respondents' body temperature. The respondent's body temperature was measured using a thermometer, according to the SOP sheet. Based on the results of statistical analysis tests with paired sample tests, the T Test showed p-value = 0.000 < 0.05 Ho was rejected and Ha was accepted where before giving onion compresses the majority of body temperature was at 37.5 ° C as many as 6 people (20%) and after giving onion compresses the majority of body temperature was at temperature 36.5°C as many as 8 people (24.7%), so it was concluded that there was an effectiveness of onion compresses on reducing body temperature in febrile infants aged 6-12 months Area of Posyandu Bawal Environment XIX Belawan Bahagia.